2016
DOI: 10.1038/tpj.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C1858T polymorphism of protein tyrosine phosphatase non-receptor type 22 (PTPN22) in children and adolescents with type 1 diabetes

Abstract: In recent years, increasing interest has been devoted to the susceptibility gene polymorphisms in type 1 diabetes (T1D) as well as in other autoimmune diseases. Among these, a nucleotide polymorphism of the gene encoding for the protein tyrosine phosphatase non-receptor type 22 (PTPN22) has been associated with T1D in several studies. The aim of this study is to define the frequency of the C1858T polymorphism in the PTPN22 gene in a cohort of 113 Caucasian patients (58 males and 55 females) with T1D, and to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“… 86 Nevertheless, numerous studies have suggested the use of PTPN22 as a prognostic factor or even as a target for novel therapeutic strategies such as treatments with LYP inhibitors, for both T1DM and AITD. 70 , 86 88 The link between PTPN22 and a spectrum of human autoimmune diseases suggests interactions between a small group of shared autoimmunity genes with HLA genotypes and other still unknown factors. 41 , 74 , 89 …”
Section: Genetics and Autoimmunitymentioning
confidence: 99%
“… 86 Nevertheless, numerous studies have suggested the use of PTPN22 as a prognostic factor or even as a target for novel therapeutic strategies such as treatments with LYP inhibitors, for both T1DM and AITD. 70 , 86 88 The link between PTPN22 and a spectrum of human autoimmune diseases suggests interactions between a small group of shared autoimmunity genes with HLA genotypes and other still unknown factors. 41 , 74 , 89 …”
Section: Genetics and Autoimmunitymentioning
confidence: 99%
“…Non‐significant differences in the stimulated C‐peptide levels between the opposite allele carriers observed by Nielsen and Pörksen were explained by the comparatively preserved capability to hyperglycaemia compensation; however, associated with an increased proinsulin level (marker of β‐cell stress) in the T allele subgroup. The contrary results of the study by Blasetti et al could reflect an impaired compensatory response of T‐cell to hyperglycaemia and DKA in the T allele carriers leading to more aggressive β‐cells destruction and an excessive release of C‐peptide.…”
Section: Discussionmentioning
confidence: 61%
“…results of the study by Blasetti et al28 could reflect an impaired compensatory response of T-cell to hyperglycaemia and DKA in the T allele carriers leading to more aggressive β-cells destruction and an excessive release of C-peptide29,30 .The unique trend of insulin secretion observed in patients with the coincidence of the PTPN22 c.1858CC and FCRL3 -169CC genotypes resulted in a tendency for these individuals to have the lowestHbA1c levels over the observation time in comparison with carriers of other genotype pairs. This indicates a better long-term prognosis and lower risk of chronic diabetes complications, as was shown in the Diabetes Control and Complications Trial (DCCT) 31 .…”
mentioning
confidence: 88%
“…This protein, a known negative regulator of T-cell signaling, is expressed in DCs as well as monocytes and macrophages. Additionally, studies have shown that a coding variant polymorphism in human PTPN22 is associated with increased risk of T1D ( 53 , 54 ). In mice, a similar polymorphism in PTPN22 leads to macrophage hyperactivation ( 55 ).…”
Section: Monocyte Expression Of Ptpn22 Potentiates T-cell Recruitmentmentioning
confidence: 99%